Palliative care: "It is OK to be not OK" - Kustanti, Christina Yeni; Nobe, Naoko (The Journal of Palembang Nursing Studies, 2024)
Palliative care is in demand as more people are diagnosed with life-threatening illnesses. Palliative care provides primary, end-of-life, and bereavement care, considering the diversity of patients’ cultural backgrounds. Various strategies have been developed and investigated to improve care access for the targeted populations. Additionally, palliative care is intended to help patients live well till death. While death is inevitable, it is nonetheless essential to life. However, some people still struggle to discuss their life-threatening conditions and accept receiving the appropriate palliative care. Notwithstanding the multitude of palliative care guidelines, the public’s limited understanding or misconceptions concerning palliative care pose a significant obstacle for healthcare workers in delivering effective palliative care services. Therefore, it is critical to continue advocating for palliative care services, as each and every person deserves to experience a quality of life until their final moments. While being diagnosed with a life-threatening illness may be an unpleasant experience, it is acceptable to discuss it to allow others, including healthcare workers, the chance to offer appropriate support.